Developing a digital data platform for surveillance of food and water-borne pathogens in North East India: insight for public health advocacy - Das, Samaresh; Kaur, Harleen; Mukherjee, Subhankar; Chakraborty, Manas; Gupta, Raja; Roy, Shalony; Ganguly, Indranil; Majumdar, Tapan; Dolma, Karma Gyurmey; Sharma, Pallab; Chaliha Hazarika, Suranjana; Modi, Dalem; et al. (Frontiers in Public Health, 2024)
Robust digital infrastructure is vital and the need of the hour, especially in the healthcare sector, for real-time data generation, analysis, and quick decision-making. Food- and water-borne illnesses represent a prominent cause of morbidity and mortality worldwide. India, a developing nation with diverse cultures and food practices, poses a high risk of food-borne diseases and outbreaks, yet is often underreported and ineffectively researched. Also, the unique socio-economic and environmental factors of the Northeast (NE) region contribute to the high burden of food-borne diseases. To address these trepidations, the Indian Council of Medical Research (ICMR) has undertaken a study for the surveillance of food-borne pathogens in NE India. The present study focuses on the development of a digital database system for the systematic surveillance of foodborne disease outbreaks, aiming to address the gaps in traditional surveillance methods and improve disease detection and response capabilities. The digital system integrates mobile applications, web-based platforms, and advanced analytics tools to enable real-time data collection, dissemination, and analysis of food-borne illness data. Additionally, the secure and scalable nature of the system enhances data accuracy and accessibility, making it a valuable tool for enhancing food-borne disease surveillance efforts in resource-constrained settings.